CONSTRUCT OF WOMEN, VIOLENCE, AND LIBERATION OF IDENTITY IN "FIKSI." FILM - Zainal Abidin Achmad (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2020)
Film "fiksi." is one of the Indonesian films that convey a message about the importance of caring for family harmony. This qualitative research uses the John Fiske semiotic method, with a corpus on the behavior of the main character Mia (played by Ladya Cheryl) as herself. The method is suitable for examining texts, images, and symbols that have a cultural connection to particular social contexts. The theory of social reality construction and representation is useful for exploring interpretations of the symbols and signs displayed in the film. Scenes that become the corpus include Mia's speech, actions, and decisions in resolving problems and getting their goals. The analysis uses three levels, first the level of reality that examines: physical appearance, clothing, cosmetology, setting, gestures, the intonation of sounds, and facial expressions. Second, the level of representation that looks at the position of the camera, lighting, musical system, and editing. Third, the level of ideology that examines the values and ideologies implied through dialogue. Mia's various acts of violence, such as cheating, manipulating, beating, strangling, and killing, shows the liberation of her identity as a woman. Despite giving appreciation to the figure of the man she loved, the character Mia took action and carried out her decision as her own choice. The construction of women in Mia is a woman who has full authority over her body and mind. A woman who is the subject and sets her line of life. Keywords: Gender and Media; Liberation of Identity; Cultural Studies; Representation